Crochet a flower bouquet : 35 crochet patterns for handmade flowers and foilage - Li, Li (Founder of Lilyrosy) (David & Charles Publishing, 2025)
"A collection of crochet patterns for 3 dimensional flowers and foliage which can be used to create beautiful floral bouquets to display at home or gift to friends and family. This practical guide to crochet flowers explains how to make and construct 35 different types of flowers and foliage including all the most popular flowers and plants. These can then be combined in endless combinations to create wonderful bouquets to display at home or to give as gifts. Crochet A Flower Bouquet includes: Crochet patterns and charts for 35 flowers and foliage including all the classic flowers and some more unusual blooms. Step-by-step instructions for how to construct the finished blooms and attach the flower heads and leaves to stems for the most life-like results. Five themed bouquet projects using different combinations of the flowers and foliage including a stunning wedding bouquet. This unique collection of crochet patterns for beautifully lifelike blooms offers endless possibilities for combining different flowers and foliage to create bespoke floral bouquets to treasure forever. Delight friends and family with a wonderful gift of crocheted flowers for special occasions and enjoy making all 35 flowers and plants."--Publisher.